2017 Water and Sewerage Sector : Private Participation in Infrastructure - World Bank Group (World Bank, Washington, DC, 2018)
In 2017, 30 projects in the water and sewerage sector received a total of USD 1.9 billion in investment—a decline of seven percent from 2016 levels. This not only marks the second-lowest level of investment in the previous 10 years (after the USD 1.2 billion recorded in 2011), but is also 55 percent lower than the five-year average investment level of USD 4.2 billion. The investment peak of USD 6.0 billion in 2012 was due to a substantial amount of investment (USD 5.4 billion) in LAC. A second peak in 2015 was the result of USD 3.1 billion worth of investment in LAC and a USD 1.2-billion investment in Russia. The declining levels of sectoral investments in recent years are largely explained by the muted investments in these regions. The PPI investment commitment in this sector in 2017 accounted for only two percent of the total PPI investment, compared to 3.8 percent over the previous five years, and three percent over the previous 10 years. On the brighter side, 2017 marked a 21-percent increase in investments in water-treatment plants, which accounted for 84 percent of sectoral investments (USD 1.6 billion out of USD 1.9 billion). It is also 50-percent higher than the average investment in water-treatment plants in the previous five years. China accounted for four-fifths of investments in water-treatment projects, with the majority of these being greenfield projects. 2017 WATER & SEWERAGE SECTOR On the other hand, the water-utility subsector received the lowest level of investment of the previous 10 years; this was the primary cause for the drop in sectoral investments in recent years. There were only three water-utility projects, with a total worth of USD 291 million.Interestingly, the water sector saw a large percentage of contracts granted at the local or municipal levels. Over the previous 10 years, an average of 77 percent of contracts were granted at the local and municipal levels, whereas for other sectors, a majority of contracts were granted at the national level. In 2017, 22 of 30 projects were contracted by local or municipal governments. Twenty-one of these projects were in China; they amounted to USD 1.06 billion, and 20 of them were treatment plants. Of the four projects that were contracted by state or provincial governments, three were from China and amounted to USD 365 million. Brazil had one project (worth USD 3.4 million) contracted by a local or municipal government, and one project (worth USD 215 million) by a state or provincial government. There were also individual projects seen in India, Indonesia and Rwanda that were commissioned by the national government.